RECENT ADVANCEMENT OF NANOMATERIAL IN DIAGNOSTIC AND TREATMENT OF NEUROLOGICAL AND PSYCHIATRIC DISORDERS - Shah, Muhammad Raza (Journal of Pakistan Psychiatric Society, 2022)
Nanomaterials are materials that have at least one dimension with less than approximately 100 nanometers. Variety of nanomaterials are used to treat the neurological and psychiatric disorders for example liposomes, carbon based nanotubes, Quantum dots and nanoparticles etc. are example of nanomaterials that showed significantly positive results. Due to high sensitivity, selectivity, surface area and ability to cross BBB scientist are more relaying on these materials for diagnostic and therapeutic approach towards the brain disorders because of complex structure and barriers in which brain is naturally protected. Here in our paper we are focusing on recent advancement that are made recently in order to light up the diagnostic and therapeutic application of nanomaterials with respect to neurological and psychiatric disorders.